Expérience d'immigration de Francophones en contexte linguistique minoritaire au Canada : défis et répercussions sur la santé mentale - Archambault, Hélène; de Moissac, Danielle; Levesque, Annabel; Kinkumba, Babou; Gueye, Ndeye Rokhaya; Tempier, Raymond; Alimezelli, Hubert Tote (Reflets, 2021)
Résumé Cet article explore les défis rencontrés par de nouveaux arrivants francophones à leur arrivée dans une communauté francophone en situation minoritaire au Canada, les répercussions qui en découlent et les facteurs modérateurs ayant une incidence sur leur intégration. Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante adultes immigrants ou réfugiés. Le défi principal auquel sont confrontées ces personnes est la barrière linguistique ; elle vient amplifier les défis liés à l’intégration sociale et la recherche de l’emploi. L’expérience migratoire a aussi une répercussion sur la santé mentale, sur les relations avec les proches et sur la santé physique. Le soutien social et la résilience personnelle favorisent l’adaptation dans la communauté d’accueil. Mots-clés : immigration, francophones, intégration, contexte linguistique minoritaire Abstract This article explores challenges that Francophone newcomers face at their arrival in a francophone community in a minority context in Canada, as well as the impact of these obstacles on, and moderating factors associated to, the integration process. A qualitative research was conducted, using semi-structured interviews with sixty immigrants or refugees in three Canadian cities. The most challenging obstacle is the language barrier, as it has a direct impact on social integration and employment-seeking. The migration experience also has an impact on mental health, interpersonal relationships and physical health. Social support and personal resilience foster adaptation into the host community. Keywords: immigration, francophones, integration, linguistic minority context

État des lieux de l'accès aux services de santé et des besoins en soins des nouveaux arrivants à Saint-Jean de Terre-Neuve - Deschênes-Thériault, Guillaume; Cimon, Virginie (Sociopol et a Fédération des francophones de Terre Neuve et du Labrador (FFTNL), 2025)
Parmi les enjeux auxquels font face les nouveaux arrivants à Terre-Neuve-et-Labrador se trouvent les difficultés d’accès à des soins de santé en français, situation qu’acerbe la pénurie du personnel en santé francophone. Le RSFTNL de la Fédération des francophones de Terre-Neuve et du Labrador (FFTNL), en collaboration avec Compas, le service d’établissement en immigration francophone, et la firme Sociopol, ont consulté douze personnes installées dans la ville de Saint Jean de Terre-Neuve depuis au moins six mois qui détiennent une résidence temporaire ou permanente. Les données, qui ont été collectées au moyen d’entrevues individuelles, ont permis de dégager des grandes tendances en ce qui a trait aux préoccupations en matière de santé des personnes immigrantes, et de mettre en lumière les défis auxquels elles font face pour accéder à des services de santé, comme le manque de médecin de famille, l’absence de services en français, le manque d’information et les longs délais d’attente.

Barriers to and enablers of attendance at diabetic retinopathy screening experienced by immigrants to Canada from multiple cultural and linguistic minority groups - van Allen, Zack; Dogba, Maman Joyce.; Brent, Michael. H.; Bach, Catherine; Grimshaw, Jeremy. M.; Ivers, Noah. M.; Wang, Xiaoqin.; McCleary, Nicola.; Asad, Sarah.; Chorghay, Zahraa.; Hakim, Hina; Sutakovic, Olivera; et al. (Diabetic medicine, 2020)
Aim To identify barriers to/enablers of attendance at eye screening among three groups of immigrantsto Canada from cultural/linguistic minority groups living with diabetes. Methods Using a patient-oriented research approach leveraging Diabetes Action Canada's patient engagement platform, we interviewed a purposeful sample of people with type 2 diabetes who had immigrated to Canada from: Pakistan (interviews in Urdu), China (interviews in Mandarin) and French-speaking African and Caribbean nations (interviews in French). We collected and analysed data based on the Theoretical Domains Framework covering key modifiable factors that may operate as barriers to or enablers of attending eye screening. We used directed content analysis to code barrier/enabler domains. Barriers/enablers were mapped to behaviour change techniques to inform future intervention development. Results We interviewed 39 people (13 per group). Many barriers/enablers were consistent across groups, including views about harms caused by screening itself, practical appointment issues including forgetting, screening costs, wait times and making/getting to an appointment, lack of awareness about retinopathy screening, language barriers, and family and clinical support. Group-specific barriers/enablers included a preference to return to one's country of birth for screening, the impact of winter, and preferences for alternative medicine. Conclusion Our results can inform linguistic and culturally competent interventions to support immigrants living with diabetes in attending eye screening to prevent avoidable blindness.